MicroRNAs in the oriental fruit fly, Bactrocera dorsalis: extending Drosophilid miRNA conservation to the Tephritidae. (December 2015) - Calla, Bernarda; Geib, Scott
Abstract Background The oriental fruit fly, Bactrocera dorsalis, is an important plant pest species in the family Tephritidae. It is a phytophagous species with broad host range, and while not established in the mainland United States, is a species of great concern for introduction. Despite the vast amount of information available from the closely related model organismDrosophila melanogaster, information at the genome and transcriptome level is still very limited for this species. Small RNAs act as regulatory molecules capable of determining transcript levels in the cells. The most studied small RNAs are micro RNAs, which may impact as much as 30 % of all protein coding genes in animals. Results We have sequenced small RNAs (sRNAs) from the Tephritid fruit fly, B. dorsalis (oriental fruit fly), specifically sRNAs corresponding to the 17 to 28 nucleotides long fraction of total RNA. Sequencing yielded more than 16 million reads in total. Seventy five miRNAs orthologous to known miRNAs were identified, as well as five additional novel miRNAs that might be specific to the genera, or to the Tephritid family. We constructed a gene expression profile for the identified miRNAs, and used comparative analysis withD. melanogaster to support our expression data. In addition, several miRNA clusters were identified in the genome that show conservancy withD. melanogaster . Potential targets for the identified miRNAs were also searched. Conclusions The data presented here adds to our growing pool of information concerning the genome structure and characteristics of true fruit flies. It provides a basis for comparative studies with other Dipteran and within Tephritid species, and can be used for applied research such as in the development of new control strategies based on gene silencing and transgenesis.